2021
DOI: 10.3390/e23080958
|View full text |Cite
|
Sign up to set email alerts
|

Local Analysis of Heterogeneous Intracellular Transport: Slow and Fast Moving Endosomes

Abstract: Trajectories of endosomes inside living eukaryotic cells are highly heterogeneous in space and time and diffuse anomalously due to a combination of viscoelasticity, caging, aggregation and active transport. Some of the trajectories display switching between persistent and anti-persistent motion, while others jiggle around in one position for the whole measurement time. By splitting the ensemble of endosome trajectories into slow moving subdiffusive and fast moving superdiffusive endosomes, we analyzed them sep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 55 publications
(74 reference statements)
1
35
0
Order By: Relevance
“…166 Some concrete biophysical examples of FBM-type motions are as follows. The physical mechanisms potentially underlying the anomalous dynamics of (i) potassium channels in the plasma membrane, 167 (ii) intracellular transport of insulin granules, 96 (iii) envelope glycoprotein gp41 transmembrane proteins of human-immunodeficiency virus in the T-cell plasma membranes, 1 (iv) subdiffusion of chromosomal loci in bacterial cells, 156 (v) subdiffusion of endogenous lipid granules in the living cells of fission yeast, 157 (vi) lysosome and endosome intracellular movements [describable by FBM with a stochastic Hurst exponent], 12,19 to name a few, see Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…166 Some concrete biophysical examples of FBM-type motions are as follows. The physical mechanisms potentially underlying the anomalous dynamics of (i) potassium channels in the plasma membrane, 167 (ii) intracellular transport of insulin granules, 96 (iii) envelope glycoprotein gp41 transmembrane proteins of human-immunodeficiency virus in the T-cell plasma membranes, 1 (iv) subdiffusion of chromosomal loci in bacterial cells, 156 (v) subdiffusion of endogenous lipid granules in the living cells of fission yeast, 157 (vi) lysosome and endosome intracellular movements [describable by FBM with a stochastic Hurst exponent], 12,19 to name a few, see Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The transport coefficients and scaling exponents were found to be strongly positively correlated. 19 bk With a pronounced negative peak for a slow subpopulations of the tracers.…”
Section: Pccp Papermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one can take into account multiplicative noises that might lead to noise-induced transitions [25] for a nonlinear cutoff switch model [18]. It would be interesting to take into account the stochastic anomalous intracellular transport of viruses and nanoparticles along microtubules to the perinuclear region [26][27][28][29]. Certainly, the anomalous endosomal movements have implications on their fusion and fission inside cells and therefore Rab5 to Rab7 conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent applications and experimental data-analysis studies have shown the importance of systems with "diffusing diffusivity" in anomalous diffusion, modeled with fractional, standard Brownian motions and distributed-order operators [18][19][20]. The theory of the calculus of variations for distributed-order fractional systems was initiated in 2018 by Almeida and Morgado [11], and it has been extended by the authors in 2020 to the more general framework of optimal control [12].…”
Section: Discussionmentioning
confidence: 99%